2005
DOI: 10.1097/00002820-200509000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Alternative Treatment in Cancer Patients in Turkey

Abstract: This study was designed to measure the frequency at which Turkish patients with cancer resort to complementary and alternative medicine (CAM). A total of 704 patients referred to the Gülhane Military Medical Academy and Ankara Numune Training Hospital between September 2002 and January 2003 were asked about the CAM therapies they used. Of these, 276 patients (39.2%) had used CAM. Gender, marital status, educational status, age, financial status, severity of pain, history of cancer in the family, and their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
5
13
0
8
Order By: Relevance
“…A considerable percentage (36%) of our patients indicated that they used CAM. Although this figure is in accordance with previous studies [3,5,8,[12][13][14][15][16], it is considerably lower than some large series from the UK and the US [4,6,7,17]. Cultural background and traditional differences may explain this relatively less prevalent use of CAM in northwestern Gulluoglu/Cingi/Cakir/Barlas Turkey.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A considerable percentage (36%) of our patients indicated that they used CAM. Although this figure is in accordance with previous studies [3,5,8,[12][13][14][15][16], it is considerably lower than some large series from the UK and the US [4,6,7,17]. Cultural background and traditional differences may explain this relatively less prevalent use of CAM in northwestern Gulluoglu/Cingi/Cakir/Barlas Turkey.…”
Section: Discussionsupporting
confidence: 90%
“…There are previous studies from Turkey describing the patterns of CAM use among both adult and pediatric oncology patients [12][13][14][15]. However, those studies used samples that were different to ours.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…30 It is 35.9% in Europe 8 and ranges between 32.0% and 62.1% in Turkey. 11,26,[31][32][33][34][35][36] We also found a proportion of 38.3% for CAM use, which is similar to that of literature values.…”
Section: Discussionsupporting
confidence: 88%
“…Işıkhan et al (2005) found that herbal producuts and massages are options often used by cancer patients to relieve pain. It is said that massages enable relaxation for cancer patients by decreasing the perception of the severity of the pain and anxiety (14).…”
Section: Cancer Pain: Knowledge and Experiences From The Perspective mentioning
confidence: 99%